Place Names as Source Material in the Derivation of Selected Yorùbá Riddles: A Sociological Approach - Ridwan Akinkunmi Rabiu (Journal of linguistics, culture and communication, 2024)
This work examined the place of naming, most especially place name in the derivation of Yoruba riddle known as “àlọ́ àpamọ̀”. The main thrust of this work is to examine and analyse the importance of place names as source material in the derivation of selected Yoruba riddles. The aim of this work is to examine the role place names play in the derivation and construction of Yoruba riddles. The theory adopted for this work is the sociological theory of literature and the model adopted under this theory is the mirror image approach which sees literature as the reflection of the society. Data for this research work were gathered from oral documentation through structured interviews and informal gathering of data in different social gatherings. The researcher also makes use of relevant data from existing literatures on Yoruba riddles such as Ajayi (1990), Akinyemi (2015) etc. Some of the place names that are used in the derivation of some Yorùbá riddles as analysed include important cities such as Ìbàdàn, Ọ̀yọ́, Ilé-Ifẹ̀ and Ìkòyí. From the research carried out, the researcher observed the followings (i) place-name derive Yoruba riddles mirror the habit, traits and character of the people of the towns and cities whose names were used in the derivation of the riddles. It was observed that place-name derived Yoruba riddles can be classified as a distinct type of riddle. It was also discovered that place-name derive Yorùbá riddles are sources of historical construction and reconstruction, purveyor of Yoruba culture and system of government. In conclusion, it is established that place name serves as source of derivation for Yoruba riddles and can be used as an instrument of oral histography.